Evaluation of the Effect of Rauwolfia vomitoria on Visuospatial and Cognitive Functions in Mice - Enene, Esu Ukpai; Odey, Agnes I.; Ukoh, Imoh; Mobisson, Samuel (Darul Yasin Al Sys, 2025)
Background: Due to the detrimental and adverse effect intense oxidative stress has on the brain resulting in cognitive function impairment. Hence, this study to evaluate the effect of Rauwolfia vomitoria on visuospatial and cognitive function in mice. Methods: Thirty (30) Swiss male albino mice weighing 19 to 35g were randomly assigned into three groups (A to C) ten mice each and treated as follows: Group A served as the control, Group B received 3-NP 20mg/kg via intraperitoneally for 5 days, Group C received 3-NP 20mg/kg intraperitoneally and Rauwolfia vomitoria 15mg/kg orally. Treatment was for 21 days and thereafter, neurobehavioral studies for visuospatial learning and memory was assayed using the Morris water maze test while cognition was evaluated using the novel object recognition test. IBM SPSS statistical software version 20, was used to analyze the data (P-value=<0.05) Results: 3-NP 20mg/kg significantly impaired cognition, as evidenced by decreased total exploration time, decreased index of habituation and decreased index of discrimination in the novel object recognition test. And also 3-NP caused impairment in visuospatial learning as evidenced by decreased retention quadrant duration, decreased annulus acquisition duration and decreased annulus reversal. Rauwolfia vomitoria treated group significantly ameliorated the visuospatial and cognitive impairments induced by 3-NP. Conclusions: It is based on these results, we draw the conclusion that R. vomitoria may possess memory enhancing property that resulted in the reversal of the visuospatial and cognitive decline in the Rauwolfia vomitoria (15mg/kg) treated group.